2009
DOI: 10.1080/09638280902822278
|View full text |Cite
|
Sign up to set email alerts
|

Activity focused and goal directed therapy for children with cerebral palsy – Do goals make a difference?

Abstract: GDT demonstrated clear gains for children with cerebral palsy in everyday activities and gross motor function in comparison to AT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(138 citation statements)
references
References 32 publications
5
126
0
4
Order By: Relevance
“…2,3 Several research studies have evaluated the effects of goal-setting in physical therapy of children with cerebral palsy. [4][5][6][7][8][9] The results of a recent systematic review, however, could not provide support for the effectiveness of goal-setting within an activity-focused approach on treatment outcome. 10 The authors of this review found that none of the included studies were designed specifically to determine the effect of goal-setting per se, as goalsetting was additional to guiding the interventions.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Several research studies have evaluated the effects of goal-setting in physical therapy of children with cerebral palsy. [4][5][6][7][8][9] The results of a recent systematic review, however, could not provide support for the effectiveness of goal-setting within an activity-focused approach on treatment outcome. 10 The authors of this review found that none of the included studies were designed specifically to determine the effect of goal-setting per se, as goalsetting was additional to guiding the interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, such a program should incorporate the parents' needs. To achieve the best results in children with unilateral spastic CP, we assumed that training should (a) be focused on children with unilateral CP, (b) take place in a challenging environment, (c) be sufficiently intensive and given in a relatively short period, (d ) preferably take place among peers, (e) focus on meaningful activities, ( f ) start with unilateral training feasible for young children (mCIMT), and (g) end with goal-directed, 16,17 task-specific 18 bimanual training (BiT) to integrate the activated upper limb functions in age-appropriate skills. The objective of this study was, therefore, to investigate whether 6 weeks of mCIMT followed by 2 weeks of bimanual training (mCIMT-BiT) in children with unilateral spastic CP improves the spontaneous use of the affected limb in both qualitative and quantitative terms more than usual care (UC) of the same duration.…”
Section: Constraint Induced Movement Therapy (Cimt)mentioning
confidence: 99%
“…Law et al' s 39 findings are consistent with other studies of functional therapy or task-based training EE approaches known to be effective in older children. 55,56 In line with the International Classification of Functioning, Disability, and Health, functional therapy or task-based training EE approaches deliberately consider the impact of the environmental context in the design and implementation of therapy. The difference with Law et al' s 39 context-focused study is that 2 novel approaches are compared: "hands off and hands on."…”
Section: Figurementioning
confidence: 99%